Unnecessary complexity of home medication regimens among seniors - Lindquist, Lee A.; Lindquist, Lucy M.; Zickuhr, Lisa; Friesema, Elisha; Wolf, Michael S. (Patient education and counseling, 2014)
To determine whether seniors consolidate their home medications or if there is evidence of unnecessary regimen complexity. Face-to-face interviews were conducted with 200 community-dwelling seniors >70 years in their homes. Subjects demonstrated how they took their medications in a typical day and the number of times a day patients would take medications was calculated. A pharmacist and physician blinded to patient characteristics examined medication regimens and determined the fewest number of times a day they could be taken by subjects. Home medication regimens could be simplified for 85 (42.5%) subjects. Of those subjects not optimally consolidating their medications, 53 (26.5%) could have had the number of times a day medications were taken reduced by one time per day; 32 (16.0%) reduced by two times or more. The three most common causes of overcomplexity were (1) misunderstanding medication instructions, (2) concern over drug absorption (i.e. before meals), and (3) perceived drug–drug interactions. Almost half of seniors had medication regimens that were unnecessarily complicated and could be simplified. This lack of consolidation potentially impedes medication adherence. Health care providers should ask patients to explicitly detail when medication consumption occurs in the home.